Evaluación de la difusión de la rendición de cuentas de la Gobernación de Loja: caso área urbana del cantón Loja. - Jaramillo Merino, Raquel Itamar (2024)
Accountability is a process through which representatives of public institutions make citizens participate in the management of state assets during their administration, for which an effective plan of dissemination and publicity of this process must be applied, with the main purpose of reaching citizens and generating interest in being part of the process of citizen participation and social control in the fight against corruption. The present study focuses on determining if there is an adequate application of the principle of dissemination and publicity of accountability by the Governor's Office of Loja and its impact on the knowledge of the population of the urban area of Loja regarding accountability processes. For this purpose, a mixed-order, qualitative descriptive-documentary research was carried out at the institution under study, where it was determined that the institution actually partially complies with the implementation of accountability, Although the process of accountability is technically carried out, there is no adequate planning to achieve efficient publicity and dissemination of this process. On the other hand, a quantitative methodology was used, through the application of a survey to a sample of 384 citizens of the urban area of Loja canton; the results show the scarce publicity given to citizens in the accountability process, which demonstrates the very low knowledge of citizens regarding this issue, which ultimately leads to disinterest and low participation of citizens in being part of the accountability carried out by the institution.